Molecular Signature of miR-34a/NEAT-1/p53 Axis in Mycosis Fungoides - Reham Fares; Shimaa M. Elasmer; Abeer Khalefa A.; Olfat G. Shaker; Samar M. El-Tahlawi; Ahmed Sabri; Sara M. Yaseen (Hindawi Limited, 2024)
Background. Mycosis fungoides (MF) is a type of cutaneous T-cell lymphoma where red rash exists on the skin. Understanding the role of miRNAs and ncRNAs in p53-response has become an open discussion, as they can regulate p53 or its downstream targets, and ncRNAs themselves. Objectives. To evaluate the serum levels of NEAT-1, miR-34a, and p53 in MF patients and its relation to healthy controls to indicate whether it has a potential role in the pathogenesis of the disease. Subjects and Methods. This prospective case-control study was carried out on 75 subjects subdivided into two groups, 35 MF patients (stages 1 and II) and 40 matched healthy controls. Their clinical investigations and serum biomarkers (NEAT-1, miR-34a, and p53) were measured. Results. There were significant elevations in the expression levels of both NEAT-1 (5.10 ± 1.16) and p53 (277.28 ± 62.02) in the serum of MF patients in comparison with controls (1.01 ± 0.031) and (194.29 ± 16.039), respectively, while the level of miR-34a tends to decrease in MF patients (0.24 ± 0.15). There are no significant difference between MF stages and the level of miR-34a, while in NEAT-1 and p53, there are significant differences with p value <0.05 between the stages and the biomarkers. There is a positive correlation between the %BSA and miR-34a and a slightly positive correlation between NEAT-1 and P53 with (r = 0.353, p=0.037) and (r = 0112, p=0.05), respectively. There were also negative correlations between disease duration and NEAT-1 with (r = −0.341, p=0.045) and between B2 microglobulin level and p53 (r = −0.373, p=0.027). Conclusion. The combination of miR-34a, NEAT-1, and p53 may be considered as potential biomarkers that play an active role in the disease process of MF for helping in its early diagnosis and stage identification as well.